1994
DOI: 10.1017/s0950268800051530
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis A virus infection among sewage workers in Singapore

Abstract: SUMMARYTo determine whether or not occupational exposure to sewage is associated with a higher seroprevalence of hepatitis A virus (HAV) infection, 600 sewage workers in Singapore were tested for total (IgG and IgM) antibody to HAV by enzyme immunoassay. Using logistic regression with stepwise procedure, the adjusted seroprevalence of sewage workers was 2-2 times higher than that of another nonoccupationally exposed population group. Seroprevalence was significantly correlated with age and educational levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Sltinh@j reported an increased occurrence of antibodies against hepatitis A virus in Danish sewage-exposed worlters (3). Heng et a1 (4) described an increased risk for hepatitis A infection among sewage workers in Singapore.…”
mentioning
confidence: 99%
“…Sltinh@j reported an increased occurrence of antibodies against hepatitis A virus in Danish sewage-exposed worlters (3). Heng et a1 (4) described an increased risk for hepatitis A infection among sewage workers in Singapore.…”
mentioning
confidence: 99%
“…They showed that the prevalance was increasing with the age, but the subjects aged 20-29 was showing the least amount of seropositivity. The change in seropositivity was associated with the development of Korea accompanied by an improvement in Age group n Anti HAV IgG positivity in Usak n (%) individual and social hygiene [14,15]. Pham et al [16] showed that the seropositivity of HAV in Canada was 1% in 8-13 ages group and increasing up to 17 % in 30-39 years group.…”
Section: Discussionmentioning
confidence: 99%
“…There were nine original epidemiologic studies on the risk of acquiring hepatitis A through occupational exposure to sewage due to work in a sewage plant (13)(14)(15)(16)(17)(18)(19)(20)(21). Cohort studies would have provided the best evidence, but we found only cross-sectional studies.…”
Section: Work Visual Display Units and Burning Eyesmentioning
confidence: 94%